Vehicle To Vehicle Physical Sidelink Shared Channel Capacity Estimation And Resource Allocation For 5g Network - Abubakar, Saadatu (2024)
5G V2V users can communicate with the neighboring vehicles using Device to Device (D2D) communication to exchange safety messages; Cooperative Awareness Message (CAM) and Decentralized Environmental Notification Message (DENM). Transmitting these messages over the same 5G V2V channel also called the Physical Sidelink Shared Channel (PSSCH) becomes a challenge to the channel capacity as the channel is heavily utilized and congested and the communication must ensure satisfying 5G V2V QoS requirements.